Intermediaries Supporting Occupational Health and Safety Improvements in Small Businesses: Development of Typology and Discussion of Consequences for Preventive Strategies. (13th September 2018) - Hasle, Peter; Refslund, Bjarke
Abstract: Intermediaries have been suggested as a potential source for improving Occupational Health and Safety (OHS) in small businesses (SBs), because SB due to their sheer number and limited managerial and financial resources typically have weak OHS management and higher occupational risks. SB furthermore typically has a reactive approach to OHS and do not seek out OHS assistance on their own. We propose, based on a large comparative study of SB and intermediaries, a general typology for intermediaries in relation to SB, and further, discuss the implications for preventive strategies in SB. We argue that there is a strong potential for improving OHS by including various intermediaries, however, the inclusion is not enough in itself. The interests of the intermediaries and the OHS improvement must be aligned, and the efforts across various intermediaries should be orchestrated among the key actors to maximize the outcome.